2015
DOI: 10.1039/c4dt03273j
|View full text |Cite
|
Sign up to set email alerts
|

An ionic liquid process for mercury removal from natural gas

Abstract: Efficient scrubbing of mercury vapour from natural gas streams has been demonstrated both in the laboratory and on an industrial scale, using chlorocuprate(II) ionic liquids impregnated on high surface area porous solid supports, resulting in the effective removal of mercury vapour from natural gas streams. This material has been commercialised for use within the petroleum gas production industry, and has currently been running continuously for three years on a natural gas plant in Malaysia. Here we report on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 42 publications
1
89
0
2
Order By: Relevance
“…2 Elemental and ICP analysis of the supported ionic liquid gave copper and chloride contents of 2.0% and 3.3% (w/w), respectively, consistent with 10 wt% loading of [C 4 mim] 2 [Cu 2 Cl 6 ]. 60 mg of the sieved adsorbent was loaded as a short packed bed into the 3 mm i.d.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…2 Elemental and ICP analysis of the supported ionic liquid gave copper and chloride contents of 2.0% and 3.3% (w/w), respectively, consistent with 10 wt% loading of [C 4 mim] 2 [Cu 2 Cl 6 ]. 60 mg of the sieved adsorbent was loaded as a short packed bed into the 3 mm i.d.…”
Section: Methodsmentioning
confidence: 89%
“…1 Recently, we demonstrated that supported chlorocuprate(II) ionic liquids were highly effective at capturing mercury from gases. 2 These supported ionic liquids have been successfully deployed in commercial scale mercury removal units in the oil and gas industry. 3,4 From our initial investigation, we proposed 2 that elemental mercury was trapped within the ionic liquid as a result of two-electron oxidation by chlorocuprate(II) anions, generating chloromercurate(II) species that were integrated as components of a new composite ionic liquid, following the scheme (with χ CuCl 2 = 0.5 in the ionic liquid 5 ):…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29]. Besides their intrinsic properties and application, MILs have also been used as ionic liquid precursors (ILPs) for inorganic nanomaterials, where the ILP acts as the solvent, the template, and the precursor for the inorganic material at the same time [19,30,31].…”
Section: Commentmentioning
confidence: 99%
“…46 Desulfurisation of gasoline by complexation of thiophene to Cu(I) in an ionic liquid has also been reported. 47 Most relevant to the present study is the recent work by Urtiaga and co-workers using CuCl dissolved in 1-hexyl-3-methylimidazolium chloride ([C 6 mim]Cl).…”
Section: -41mentioning
confidence: 99%